Analysis of interference between TD-SCDMA and WCDMA. (1st January 2013) - Ji, Chang-peng; Huang, Yun-fei
According to the standard specification of TD-SCDMA and WCDMA systems, the principle of the interference between TD-SCDMA and WCDMA systems was analysed and then introduced the methods and simulation model about system interference, including cell model, power control, path loss model and simulation parameters, etc. The coexistence interference of TD-SCDMA and WCDMA systems was simulated for speech users only in a macro-to-macro cells scenario considering 1, 920 MHz frequency used by classical Monte Carlo method. According to the simulation results, different parameters were analysed about the influence of system coexistence, and ACIR values were provided about system coexistence. It provides valuable reference for the research of hybrid network planning and optimising.